Antichambres de camps et répétitions générales: le renouveau de la mémoire des génocides dans l’extrême contemporain - Riva, SIlvia (Ponti/Ponts, 2022)
The paper intends to reflect on the reasons for the recent return of memory related to twentieth-century events not as well-known as those concerning the Shoah. The corpus consists of four novels that deal, respectively, with the Armenian genocide (A. Makine, Franco-Russian writer), the Rwandan genocide seen from Burundi (G. Faye, from Burundi writing in French), the genocide of the Herero and Nama in Namibia (E. Fontenaille, French writer) and a very recent novel by the diasporic writer from Belgium Bessora (Les Orphélins) that gives an account of an unprecedented phenomenon of racial ‘regeneration’ as a consequence of the Aryan policies conducted by the Nazi regime. The analysis of these writings will give rise to some reflections on the testimonial function contained in these narratives, which seem to account for a paradigm shift compared to the theories formulated in the so-called “Holocaust studies”. These texts talk about how to become witnesses and about a conjectural literature in dialogue not only with the submerged, but above all open to the future of the living, according to an enlarged scale worldview and through an interconnected memory